2001
DOI: 10.3141/1745-04
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Speed Displays and Rumble Strips at Rural-Maintenance Work Zones

Abstract: An evaluation of the effectiveness of speed displays and portable rumble strips at reducing speeds in rural-maintenance work zones is described. Speed displays are radar-activated signs that dynamically display approaching vehicle speeds. The devices were tested on two-lane low-volume, high-speed rural roads where maintenance activities were completed in a single day. Speed and volume data were collected for cars and trucks as they traveled through four work zones. These data were collected when no work-zone t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 1 publication
1
22
0
Order By: Relevance
“…The observed increase in speed compliance of 2.9% was within the range of 1% to 7% reported by Fontaine and Carlson (2001) in their Texas study. A slight decrease in the mean speed and a shift in the speed distribution toward lower speeds were observed but were not statistically significant.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The observed increase in speed compliance of 2.9% was within the range of 1% to 7% reported by Fontaine and Carlson (2001) in their Texas study. A slight decrease in the mean speed and a shift in the speed distribution toward lower speeds were observed but were not statistically significant.…”
Section: Discussionsupporting
confidence: 78%
“…KDOT found ATM to significantly reduce the mean and 85% speed for passenger cars and trucks (Meyer, 2000). Fontaine and Carlson (2001) evaluated the effectiveness of portable rumble strips at rural maintenance work zones in Texas. The dimensions of the rumble strips evaluated were different from the ones used in Kansas (Meyer, 2000).…”
Section: Review Of Temporary Rumble Stripsmentioning
confidence: 99%
“…The hypothesis of using the speed display is that drivers will actively slow down if they see their speeds above the posted limit. Fontaine and Carlson (2001) investigated the effectiveness of the portable speed displays at a rural-maintenance work zone on US 62 eastbound in Texas. The speed limit of the road segment was 70 mph and the traffic volume was approximately 1,000 vehicles per day.…”
Section: Speed Displaymentioning
confidence: 99%
“…vehicles travel 10 mph over posted speed limit) was up to 80%. One week after the speed displays were put into place, the percentage dropped from 80% to 44% at Figure 3.5 Work zone configuration with two speed displays (Fontaine & Carlson, 2001). the first speed display, and the percentage dropped 80% to 33% at the second speed display.…”
Section: Speed Displaymentioning
confidence: 99%
“…Between 2005 and2008, an average of 49% of road construction site worker fatalities were the result of being struck by a moving vehicle (U.S. Department of Labor, 2009). Three major factors have been identified as the cause for highway work-zone crashes: excessive vehicle speeds, driver speed variation, and driver inattention and erratic maneuvers (Fontaine & Carlson, 2001;Sarasua et al, 2007). Garber and Zhao (2001) studied the work-zone crash data in Virginia and found that most of the crashes are rear-end crashes and speed related.…”
Section: Introductionmentioning
confidence: 99%